The Influence of Social Media on the High Divorce Rate in Ternate City in the Perspective of Maqasid al-syari’ah - La ajiri, Takdir Hardani; Hammam, Muhammad Nibros; Nada, Hilmy Amjad (Jurnal Mediasas: Media Ilmu Syari’ah dan Ahwal Al-Syakhsiyyah, 2025)
The phenomenon of increasing divorce lawsuits filed by wives in Ternate City indicates a shift in social dynamics within Muslim households. One notable factor is the influence of social media on attitudes, emotions, and marital relationships. This study aims to analyze the implications of social media on the increase in divorce lawsuits and review them from the perspective of maq??id al-syar?’ah in Islamic family law. Using a qualitative approach and data collection techniques in the form of interviews and documentation, it was found that social media often triggers conflict, either through access to information in the form of legal awareness that strengthens the wife’s courage to file for divorce or because of evidence of infidelity and the tendency to compare one’s household with that of other couples (social comparison). The maq??id al-syar?’ah perspective views divorce as a form of protection for the soul, mind, and offspring that can threaten the psychological well-being of children. Maq??id al-syar?’ah does not directly legitimize divorce as the main solution, but emphasizes the importance of conflict prevention and strengthening relationships within the family. This study affirms the importance of digital literacy and an Islamic legal approach that is responsive to social change. [Fenomena meningkatnya cerai gugat oleh istri di Kota Ternate menunjukkan adanya pergeseran dinamika sosial dalam rumah tangga Muslim. Salah satu faktor yang mencolok adalah pengaruh media sosial terhadap sikap, emosi, dan hubungan suami istri. Penelitian ini bertujuan untuk mengalisis implikasi media sosial terhadap peningkatan kasus cerai gugat serta meninjaunya dalam perspektif maqashid syari’ah pada hukum keluarga Islam. Dengan pendekatan kualitatif dan teknik pengumpulan data berupa wawancara dan dokumentasi, ditemukan bahwa media sosial sering menjadi pemicu konflik, baik melalui akses informasi sebagai bentuk kesadaran hukum yang memperkuat keberanian istri menggugat cerai maupun karena adanya bukti perselingkuhan dan kecedenderungan membandingkan kehidupan rumah tangga dengan pasangan lain (social comparison). Perspektif maqashid syari’ah memandang tindakan cerai gugat ini sebagai bentuk perlindungan terhadap jiwa, akal, dan perlindungan terhadap keturunan yang dapat mengancam psikologis anak. Maqashid syari’ah tidak secara langsung melegitimasi perceraian sebagai jalan keluar utama, melainkan menekankan pentingnya pencegahan konflik dan penguatan relasi dalam hubungan keluarga. Penelitian ini menegaskan pentingnya literasi digital dan pendekatan hukum Islam yang responsif terhadap perubahan sosial.]